Your fitness-sharing is a reminder for my poor body: how fitness posts exposure on social media harms female body esteem - Yan, Xiumei; Yan, Jun; Tan, Chuhan; Fu, Yu; Wang, Shuqing (Frontiers in Psychology, 2025)
BackgroundPrior literature suggests that fitness posts exposure on social media increases female body image concerns. However, little research has been conducted to examine the effect of fitness posts exposure on female body esteem.ObjectiveGiven that, two studies were conducted to investigate how fitness posts exposure on social media exerted an influence on female body esteem.Method and resultsBy using a questionnaire survey (n = 270), we in Study 1 measured participants’ frequency of fitness posts exposure on social media, body esteem, body surveillance, and appearance contingent self-worth. The results showed that fitness posts exposure was significantly and positively related to female body esteem, and body surveillance played a mediating role between them. And this mediation was further moderated by appearance contingent self-worth. Simple slope analysis showed that fitness posts exposure had a significantly positive prediction on body surveillance at the high level of appearance contingent self-worth, but the prediction of fitness posts exposure was not significant at the low level of appearance contingent self-worth. Study 2 was a lab experiment, in which we randomly assigned 180 female undergraduates to the fitness-appearance exposure condition, the fitness-performance exposure condition, and the travel image exposure condition. Then, we asked participants to report body surveillance and body esteem. The results showed that participants in the fitness-appearance exposure condition reported higher body surveillance and lower body esteem than participants in the other two conditions. Consistent with Study 1, Study 2 revealed the mediating role of body surveillance between exposure condition and body esteem.ConclusionFitness posts exposure produces a negative influence on female body esteem via the mediation of body surveillance, and this pattern is more obvious among women with high appearance contingent self-worth. Appearance-relevant content involved in fitness posts, rather than pure fitness performance, harms female body esteem.